A phase 1/2 trial of lenalidomide and dexamethasone in adult patients with refractory/relapsed acute lymphoblastic leukemia. Issue 4 (21st April 2017) - Tavernier-Tardy, E.; Cornillon, J.; Molucon-Chabrot, C.; Cahn, J. Y.; Tinquaut, F.; Bourmaud, A.; Guyotat, D.; Thomas, X.
ABSTRACT: Objectives: Adult patients with refractory/relapsed ALL have poor survival outcomes with current chemotherapies. We aimed to determine safety and efficacy of lenalidomide, an oral immunomodulator, in these patients. Methods: This phase 1/2 trial (EUDRACT # 2009-009372-13) included 10 patients who received 28-day cycles of oral lenalidomide 25 mg/day, days 1 through 21, in combination with oral dexamethasone 40 mg/day on days 1, 8, 15, 22. Primary endpoints were tolerance and the overall response rate (ORR). Secondary endpoints included overall survival (OS) and quality of life. Results: The most common grade 3 or 4 adverse events were myelosuppression. The ORR among the participants who could be evaluated was 28.6% (95% confidence interval [CI], 0–62.2%). The median OS was 92 days (range, 43–133 days). All patients have died because of progressive disease. Quality of life remains stable during treatment cycles. Discussion and conclusion: The safety of combination therapy consisting of lenalidomide plus dexamethasone is consistent with ambulatory administration. Efficacy should be reevaluated in a larger series including patients less intensively previously treated.